Análisis del comportamiento de los usuariosen el consumo del servicio de telefonía móviles en la ciudad de Quevedo año 2012 - Vera Jiménez, María Paola (2012)
Mobile operators have become indispensable for human beings, in the Canton of the telephony Claro Quevedo and Movistar have great reception, Alegro - Cnt is positioning. The objective of this research is to analyze the behavior of users of mobile telephony service in the city of Quevedo, 2012, which will meet the requirements of demand with regard to innovations, incentives for consumption. The research methods applied are: Deductive to analyze the behavior of users, the inductive method, which helped to establish consumer preferences mobile telephony service. The technique used in this study was a survey to consumers of cellular service. According to analysis conducted by this research concludes that the service provided by operators not entirely satisfied users of the City of Quevedo and, despite this show have received most of the operators.